DAMPAK GAMIFIKASI DALAM PEMBELAJARAN BAHASA INGGRIS: The Impact Of Gamification In English Language Learning - Seventilofa, I Gusti Ngurah Octova (Yayasan Al-Amin Qalbu, 2024)
Gamification, the incorporation of game elements into non-game contexts, has emerged as a promising strategy to enhance motivation and engagement in English language learning. This type of research is library research. The research results show that, the synthesis of theoretical insights, empirical findings, and instructional considerations highlights the importance of Gamification in English Language Learning. The significance of incorporating gaming aspects into language education is highlighted by the convergence of theoretical foundations, empirical data, and instructional design considerations